2021
DOI: 10.1029/2021jd034876
|View full text |Cite
|
Sign up to set email alerts
|

Regional Characteristics of Variability in the Northern Hemisphere Wintertime Polar Front Jet and Subtropical Jet in Observations and CMIP6 Models

Abstract: Jet streams are relatively narrow bands of strong west-to-east winds in the upper troposphere. In the zonal-mean climatology, there are two jet streams, the subtropical jet (STJ) and polar front jet (PFJ), located in both the Northern Hemisphere (NH) and Southern Hemisphere (SH). The STJ is commonly viewed as being driven by the angular momentum conservation in the poleward flowing upper tropospheric branch of the tropical Hadley circulation (Held & Hou, 1980;Schneider, 1977), and thus it is located near the p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…In addition, the PDO phase change from positive to negative is related to a poleward expansion of the Hadley Cell [39,94], which drives the STJ in the same direction. This argument is supported by studies that have shown that the Northern Hemisphere Pacific STJ is mostly modulated by central Pacific SST variability [58,89,[102][103][104][105]. In summary, numerical experiments in which Arctic warming is induced by the loss of sea-ice have a consistent but limited Arctic influence on the STJ latitudinal position over Europe, North America and the North Atlantic basin.…”
Section: Discussionmentioning
confidence: 61%
“…In addition, the PDO phase change from positive to negative is related to a poleward expansion of the Hadley Cell [39,94], which drives the STJ in the same direction. This argument is supported by studies that have shown that the Northern Hemisphere Pacific STJ is mostly modulated by central Pacific SST variability [58,89,[102][103][104][105]. In summary, numerical experiments in which Arctic warming is induced by the loss of sea-ice have a consistent but limited Arctic influence on the STJ latitudinal position over Europe, North America and the North Atlantic basin.…”
Section: Discussionmentioning
confidence: 61%
“…Previous studies have shown that simulate a larger warm pool area in the present day and predicted an excessive warming in the future in the eastern tropical Pacific due to intensified ocean stratification (Park et al, 2022). Liu et al showed that CMIP6 multi‐model mean reproduces the warm pool size well, but there is large spread among models, with models with smaller warm pool areas (larger biases) tending to simulate weaker WTP SST (Liu & Grise, 2023). Therefore, there are still significant biases in the current model simulations of climate variability in the Pacific region.…”
Section: Introductionmentioning
confidence: 99%
“…This technique has been applied to constrain CMIP6 ensemble projections of surface temperature and precipitation. Several studies have used emergent constraints to reduce projection uncertainty at the global scale (Liu & Grise, 2023; Nijsse et al, 2020; Shiogama et al, 2022; Tokarska et al, 2020) and regional scale (Chai et al, 2022; Chen et al, 2020; Hu et al, 2021). The reliability ensemble averaging (REA) approach, as introduced by Giorgi and Mearns (2002), assigns weights to each model based on reliability criteria, including the “model performance” and “model convergence” criteria.…”
Section: Introductionmentioning
confidence: 99%